PENDIDIKAN AGAMA ISLAM; ANTARA TEKSTUALIS NORMATIF DENGAN KONTEKSTUALIS HISTORIS - Susanto, Edi (JURNAL TADRIS STAIN PAMEKASAN, 2009)
Abstract: This article carefully observes Islamic education bipolarly---Islamic education looked through the perspective of normative-textualist and historical-contextualist. The perspectives execute the construction of materials and Islamic education approach that would be transformed. This will determine the shape of religion character.  Both perspectives posses strong and waek points. Yet, it can be deduced that no single perspective is applicable for any situations. Consequently, religious teachers must be accurate in applying the two perspectives on the basis of contectual-persuasiveness matching to life dynamic.